Türkiye'de Yunan vahşet ve soy kırımı girişimi, 15 Mayıs 1919 - 9 Eylül 1922 - Yalazan, Talat. (Ankara)
2 c. (1. c. v, 145, [55] s. tıpkıbasım, tablo ; 2. c. vii, 196, [1] s., 1 katlı kroki, [2] s., [14] s. tıpkıbasım)